A novel intramolecular negative regulation of mouse Jak3 activity by tyrosine 820. (22nd February 2022) - Sekine, Yuichi; Kikkawa, Kazuna; Witthuhn, Bruce A; Kashiwakura, Jun-ichi; Muromoto, Ryuta; Kitai, Yuichi; Fujimuro, Masahiro; Oritani, Kenji; Matsuda, Tadashi
Abstract: Jak3, a member of the Janus kinase family, is essential for the cytokine receptor common gamma chain (γc)-mediated signaling. During activation of Jak3, tyrosine residues are phosphorylated and potentially regulate its kinase activity. We identified a novel tyrosine phosphorylation site within mouse Jak3, Y820, which is conserved in human Jak3, Y824. IL-2-induced tyrosine phosphorylation of Jak3 Y824 in human T cell line HuT78 cells was detected by using a phosphospecific, pY824, antibody. Mutation of mouse Jak3 Y820 to alanine (Y820A) showed increased autophosphorylation of Jak3 and enhanced signal transducer and activator of transcription 5 (STAT5) tyrosine phosphorylation and transcriptional activation. Stably expressed Jak3 Y820A in F7 cells, an IL-2 responsive mouse pro-B cell line Ba/F3, exhibited enhanced IL-2-dependent cell growth. Mechanistic studies demonstrated that interaction between Jak3 and STAT5 increased in Jak3 Y820A compared to wild-type Jak3. These data suggest that Jak3 Y820 plays a role in negative regulation of Jak3-mediated STAT5 signaling cascade upon IL-2-stimulation. We speculate that this occurs through an interaction promoted by the tyrosine phosphorylated Y820 or a conformational change by Y820 mutation with either the STAT directly or with the recruitment of molecules such as phosphatases via a SH2 interaction. Additional studies will focus on these interactions as Jak3 plays a crucial role in disease and health. Abstract : A novel tyrosine-phosphorylation site regulates Jak3 activity Graphical Abstract: